Correlations of isokinetic measurements with tendon healing following open repair of rotator cuff tears - Demirors, Huseyin (Springer-Verlag, 2009)
The aim of this study was to investigate the correlation of tendon integrity following open cuff repairs with functional and isokinetic strength measurements. Twenty-six shoulders of 25 patients were included in this study. At the final follow-up, 14 repairs (53.8%) were intact and 12 repairs (46.2%) had failed on magnetic resonance imaging (MRI). Mean UCLA score at latest follow-up was 28.5 and mean Constant score was 80.3. Constant scores were found to be significantly low for the failed group. Age was found to be significantly related to failed repair. Fatty infiltration stage in the failed repair group was significantly high, and a strong positive correlation for both groups existed pre and postoperatively. When both groups were compared, the failed group was found to have significantly low measurements at extension and internal rotation. Despite high failure rates, functional results were satisfactory. Increased age and fatty infiltration stage decrease success.